What does interdisciplinarity look like in practice: Mapping interdisciplinarity and its limits in the environmental sciences. (February 2018) - MacLeod, Miles; Nagatsu, Michiru
Abstract: In this paper we take a close look at current interdisciplinary modeling practices in the environmental sciences, and suggest that closer attention needs to be paid to the nature of scientific practices when investigating and planning interdisciplinarity. While interdisciplinarity is often portrayed as a medium of novel and transformative methodological work, current modeling strategies in the environmental sciences are conservative, avoiding methodological conflict, while confining interdisciplinary interactions to a relatively small set of pre-existing modeling frameworks and strategies (a process we call crystallization ). We argue that such practices can be rationalized as responses in part to cognitive constraints which restrict interdisciplinary work. We identify four salient integrative modeling strategies in environmental sciences, and argue that this crystallization, while contradicting somewhat the novel goals many have for interdisciplinarity, makes sense when considered in the light of common disciplinary practices and cognitive constraints. These results provide cause to rethink in more concrete methodological terms what interdisciplinarity amounts to, and what kinds of interdisciplinarity are obtainable in the environmental sciences and elsewhere. Highlights: This paper: finds that current integrative modeling strategies in the environmental sciences are conservative rather than transformative. characterizes the convergence of interdisciplinary practice to a small set of modeling strategies as crystallization. identifies four such strategies and analyzes how they handle cognitive obstacles which restrict interdisciplinary research. rationalizes crystallization in the light of common disciplinary practices of utilizing a limited number of model templates. calls for studies of interdisciplinarity based on history and philosophy of scientific practice.